Patient Turnover and Nursing Employment in Massachusetts Hospitals Before and After Health Insurance Reform: Implications for the Patient Protection and Affordable Care Act. (August 2013) - Shindul-Rothschild, Judith; Gregas, Matt
The Affordable Care Act is modeled after Massachusetts insurance reforms enacted in 2006. A linear mixed effect model examined trends in patient turnover and nurse employment in Massachusetts, New York, and California nonfederal hospitals from 2000 to 2011. The linear mixed effect analysis found that the rate of increase in hospital admissions was significantly higher in Massachusetts hospitals ( p  < .001) than that in California and New York ( p  = .007). The rate of change in registered nurses full-time equivalent hours per patient day was significantly less ( p  = .02) in Massachusetts than that in California and was not different from zero. The rate of change in admissions to registered nurses full-time equivalent hours per patient day was significantly greater in Massachusetts than California ( p  = .001) and New York ( p  < .01). Nurse staffing remained flat in Massachusetts, despite a significant increase in hospital admissions. The implications of the findings for nurse employment and hospital utilization following the implementation of national health insurance reform are discussed.